2019
DOI: 10.1080/15389588.2019.1606910
|View full text |Cite
|
Sign up to set email alerts
|

Acute injuries resulting from accidents involving powered mobility devices (PMDs)—Development and outcomes of PMD-related accidents in Sweden

Abstract: Objective: Powered mobility devices (PMDs) are commonly used as aids for older people and people with disabilities, subgroups of vulnarable road users (VRUs) who are rarely noted in traffic safety contexts. However, the problem of accidents involving PMD drivers has been reported in many countries where these vehicles have become increasingly popular. The aim of this study is to extract and analyze national PMD-related accident and injury data reported to the Swedish Traffic Accident Data Acquisition (STRADA) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 50 publications
1
21
0
2
Order By: Relevance
“…In one study from Singapore, ePMD-related injuries were generally found not to be severe and were primarily external wounds and upper and lower limb injuries [7]. In a Swedish study, most of the reported ePMD-related injuries resulted from the driver hitting the ground due to device turnover [8]. Few studies on ePMD-related injuries have been conducted in South Korea, however.…”
Section: Introductionmentioning
confidence: 99%
“…In one study from Singapore, ePMD-related injuries were generally found not to be severe and were primarily external wounds and upper and lower limb injuries [7]. In a Swedish study, most of the reported ePMD-related injuries resulted from the driver hitting the ground due to device turnover [8]. Few studies on ePMD-related injuries have been conducted in South Korea, however.…”
Section: Introductionmentioning
confidence: 99%
“…This knowledge may also contribute to Sweden achieving the goal of reducing the number of seriously injured road users by 25%, including pedestrian single accidents, by 2030 (The Government of Sweden, 2020). This study relates to our previous study into powered mobility devices (Carlsson & Lundälv, 2019).…”
Section: Introductionmentioning
confidence: 64%
“…Albeit, there are studies investigating more established vehicle types within the powered microvehicle taxonomy such as powered two-wheelers. There also exists a range of issues regarding microvehicle user safety and transport planning, including where they should be used within the road reserve [21,22], safe operating speeds [22][23][24] and use of safety equipment [21].…”
Section: Resultsmentioning
confidence: 99%